Current controversies in prenatal diagnosis 3: Gene editing should replace embryo selection following PGD - Wells, D; Vermeesch, JR; Simpson, JL (Wiley, 2019)
This is a written summary of the oral debate presented on July 10, 2018, at the 22nd annual meeting of the International Society for Prenatal Diagnosis, held in Antwerp, Belgium. The opinions stated were assigned and do not necessarily reflect the personal or professional opinions of the authors. Discussants are listed in the order they debated.